Caracterização higiênico-sanitária e socioambiental da pesca artesanal do Rio Apodi-Mossoró, RN - Morais, Jefferson Alves de (2016)
The river Apodi-Mossoró, there is artisanal fishing in the region near the city of Mossoro is already showing clear signs of environmental problems such as pollution from the dumping of sewage, reduction of its riparian vegetation and sedimentation. This environmental degradation worsens even more because of the degree of water contamination in the area of urban area of Mossoro. The main purpose of study is to assess the social and environmental aspects of the Z-55 colony on the Mossoro-RN river. To analyze the environmental condition of water and fish Apodi-Mossoró river, was made the quantification of total and fecal coliforms, Escherichia coli, mesophilic bacteria, Staphylococcus aureus and Salmonella sp., and the social conditions were assessed through an interview with colony of fishermen. This study was conducted in the municipality of Mossoró-RN, more precisely in Apodi-Mossoró river stretch that cuts through this city. For environmental analysis of water and fish collections were held in Apodi-Mossoró river stretch that bisects the urban area in six different geo-referenced points according to MacFaddin methodology. For social interviews with artisanal fishermen a questionnaire was administered at the headquarters of the Z-55 cologne, as well as in the homes of fishermen and Apodi-Mossoró river. The values found for the microbiological analysis of water and fish have proven unsatisfactory, showing how the river is impacted anthropically. According to the responses of interviews with artisanal fishermen, have resulted in the positive environmental perception thereof on pollution Apodi-Mossoró river. We conclude that the Apodi-Mossoró river need for further environmental monitoring as it is with your water and your fish with microbiological parameters outside the standards of the current legislation, as well as artisanal fishermen belonging to the Z-55 cologne is the perception the Apodi-Mossoró river is polluted, but unaware of the major diseases that can cause pollution